Effect of Temperature and Selection for Growth on Intracellular Lipid Accumulation and Adipogenic Gene Expression in Turkey Pectoralis Major Muscle Satellite Cells - Xu, Jiahui; Strasburg, Gale M.; Reed, Kent M.; Velleman, Sandra G. (Frontiers in Physiology, 2021)
As multipotential stem cells, satellite cells (SCs) have the potential to express adipogenic genes resulting in lipid synthesis with thermal stress. The present study determined the effect of temperature on intracellular lipid synthesis and adipogenic gene expression in SCs isolated from the pectoralis major (p. major) muscle of 7-day-old fast-growing modern commercial (NC) turkeys compared to SCs from unselected slower-growing turkeys (Randombred Control Line 2; RBC2). Since proliferating and differentiating SCs have different responses to thermal stress, three incubation strategies were used: 1) SCs proliferated at the control temperature of 38°C and differentiated at 43° or 33°C; 2) SCs proliferated at 43° or 33°C and differentiated at 38°C; or 3) SCs both proliferated and differentiated at 43°, 38°, or 33°C. During proliferation, lipid accumulation increased at 43°C and decreased at 33°C with the NC line showing greater variation than the RBC2 line. During proliferation at 43°C, peroxisome proliferator-activated receptor-γ (PPARγ) and neuropeptide-Y (NPY) expression was reduced to a greater extent in the NC line compared to the RBC2 line. At 33°C, expression of PPARγ, NPY, and CCAAT/enhancer-binding protein-β (C/EBPβ) was upregulated, but only in the RBC2 line. During differentiation, both lines showed greater changes in lipid accumulation and in C/EBPβ and NPY expression if the thermal challenge was initiated during proliferation. These data suggest that adipogenic gene expression is more responsive to a thermal challenge in proliferating SCs than in differentiating SCs, and that growth-selection has increased temperature sensitivity of SCs, which may significantly affect breast muscle structure and composition.